PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA TRANSPORTASI ONLINE PADA MAHASISWA UT BEKASI - Christopher, Ferdyan; Anwar, Amelia (Universitas Banten Jaya, 2024)
ABSTRACT In the current digital era, online transportation services have become an important part of everyday life, especially among students. With the existence of various online transportation applications such as Grab, Uber, and Gojek, students have more options to choose a mode of transportation that suits their needs and budget. In this case, service quality and promotion are important factors that influence students' decisions to purchase online transportation services. The aim of this research is to determine the influence of promotions and service quality on the decision to purchase online transportation services among UT Bekasi students. The research used quantitative methods, collection techniques using the questionnaire method, the number of samples in this research was 99 students at the Open University in the city of Bekasi. Data analysis using multiple linear regression, the results concluded that partially and simultaneously promotion and service quality had a significant effect on the decision to purchase online transportation services among UT Bekasi students, with a predictive ability of 56.6%, while the remaining 43.4% was the decision to purchase transportation services. Online learning for UT Bekasi students is influenced by other factors not examined in this research.